2016
DOI: 10.1016/j.matbio.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase 2 regulates fibroblast senescence in pulmonary fibrosis

Abstract: Dysregulated repair of lung injury often results in lung fibrosis characterized by unremitting deposition of matrix components including the glycosaminoglycan hyaluronan (HA). HA is mainly produced by hyaluronan synthases (HAS) in mesenchymal cells. We previously demonstrated that over-expression of HAS2 in mesenchymal cells in mice regulates the invasiveness of fibroblasts and promotes severe lung fibrosis. The mechanisms that control the resolution of lung fibrosis are unknown. We propose that a critical ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 61 publications
(107 reference statements)
0
66
0
Order By: Relevance
“…The progressive loss of dermal hyaluronan is a hallmark of skin aging. A major factor that contribute to this loss is the aging-associated downregulation of HAS2 and HAS3 [8, 9]. Moreover, we measured the expression of the senescence-associated genes p53 [10], p21 upregulation [11], maspin[12], and IL-6 [13].…”
Section: Methodsmentioning
confidence: 99%
“…The progressive loss of dermal hyaluronan is a hallmark of skin aging. A major factor that contribute to this loss is the aging-associated downregulation of HAS2 and HAS3 [8, 9]. Moreover, we measured the expression of the senescence-associated genes p53 [10], p21 upregulation [11], maspin[12], and IL-6 [13].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies by Paul Noble’s group have demonstrated that overexpression of HAS2 in murine mesenchymal cells regulates the invasiveness of fibroblasts and promotes pulmonary fibrosis [210]. Furthermore, this same group has shown that HAS2 controls fibroblast senescence [211] and that targeting HAS2 could be an attractive therapeutic approach to resolve tissue fibrosis. These studies however have been further complicated by studies from our own group [212] which showed that removal of hyaluronan from TGF-β-stimulated myofibroblasts promotes the fibrotic phenotype by increasing, rather than inhibiting, the expression and accumulation of collagen I and fibronectin (Figure 6).…”
Section: Dynamic Ecm Remodeling Of Hyaluronan and Versican: From Provmentioning
confidence: 99%
“…As one member of the HAS family, HAS-2 is also involved in synthesizing hyaluronan and cell proliferation, cell differentiation and even cellular inflammation [16]. In particular, the inhibition of HAS-2 in tumor cells would influence the cell cycle to further control cell proliferation [17]. HAS-2 has been reported to be over-expressed in breast cancer, and HAS-2 was demonstrated to be involved in the migration and invasion of breast cancer cells, suggesting that it might play a role in breast cancer metastasis [18,19].…”
Section: Introductionmentioning
confidence: 99%